Research on borehole stability of shale based on seepage-stress-damage coupling model (Fracture and Structural Integrity, 2013)
In oil drilling, one of the most complicated problems is borehole stability of shale. Based on the theory of continuum damage mechanics, a modified Mohr-Coulomb failure criterion according to plastic damage evolution and the seepage-stress coupling is established. Meanwhile, the damage evolution equation which is based on equivalent plastic strain and the permeability evolution equation of shale are proposed in this paper. The physical model of borehole rock for a well in China western oilfield is set up to analyze the distribution of damage, permeability, stress, plastic strain and displacement. In the calculation process, the influence of rock damage to elastic modulus, cohesion and permeability is involved by writing a subroutine for ABAQUS. The results show that the rock damage evolution has a significant effect to the plastic strain and stress in plastic zone. Different drilling fluid density will produce different damage in its value, range and type. This study improves the theory of mechanical mechanism of borehole collapse and fracture, and provides a reference for the further research of seepage-stress-chemical-damage coupling of wall rock.
Keywords: Borehole stability